DEVELOPMENT OF HAPPINESS SUFISM SCALE USING CONFIRMATORY FACTOR ANALYSIS - Ernawati (Program Studi Psikologi Islam, 2025)
Some research related to the concept of happiness is still conducted with a Western psychological approach, or known as psychological well-being. Some instruments or measures are developed conceptually and operationally from positivistic psychology. These approaches are still general, so they are sometimes unable to fully explain aspects of happiness in communities with certain cultural values, such as religiosity, because they ignore aspects of spirituality. As a result, psychological theories related to the concept of happiness are not very appropriate when applied in a societal context or elsewhere, because the concept of happiness itself is considered to be value-biased. For example, religious values certainly differ in how they view the concept of happiness, so that the measurement results become invalid and unreliable when used in Islamic communities with strong characteristics of the Sufi tradition. Meanwhile, there has been little research on the attainment of happiness, which is approached in an Islamic (deductive) way, through understanding oneself, God, the world and the hereafter. This research examines the concept of happiness discussed by one of the Sufi figures, Al-Ghazali, namely Kimiyatus Sa'adah. This research carried out the construction of Al-Ghazali's Sufi happiness and then quantitatively tested the validity and reliability using the Confirmatory Factor Analysis (CFA) method. This construction results in Sufism happiness being composed of 3 aspects, including: knowledge about yourself, placing your heart as your leader, and knowledge of God. The instrument was distributed to 93 students of Sufism and Psychotherapy at UIN Walisongo Semarang, and the results showed that there were 26 items that met the valid criteria, consisting of: aspect 1 (knowledge about yourself) is measured with 9 statement items, aspect 2 (placing your heart as your leader) is measured with 7 statement items, and aspect 3 (knowledge of God) is measured with 10 statement items. Based on the reliability criteria, both internal reliability and composite reliability, it can be said that the construct model formed meets the reliability assumptions.